Towards Adaptive Cybersecurity in Smart Cities: Threat Trends, Mitigation Strategies, and Future Scenarios - Egi Al Fansyah; Muharman Lubis; Muhammad Dwi Hary Sandy (Journal of Information Systems and Technology, 2026)
Smart Cities, which represent modern technology-based urban environments, are currently faced with significant challenges concerning cybersecurity. Cyber threats targeting the digital infrastructure and sensitive data within Smart Cities continue to evolve alongside the increasing levels of connectivity and reliance on technology. Various types of attacks, such as Distributed Denial of Service (DDoS), Ransomware, and exploitation of Internet of Things (IoT) devices, have become threats that warrant serious attention. Therefore, the implementation of effective mitigation strategies is essential to safeguard the security of Smart Cities. This paper examines various potential cyber threats that could jeopardize Smart Cities and evaluates the effectiveness of mitigation strategies that have been implemented, such as the adoption of the Zero Trust model, multi-factor authentication, and real-time anomaly detection systems. Furthermore, this paper discusses recent research developments in threat mitigation technologies, including the utilization of artificial intelligence and blockchain. Findings from this analysis indicate that, in order to ensure the sustainability and security of Smart Cities, more stringent policies, cross-sector collaboration, and ongoing research in mitigation technology development are required.